Evaluasi Kebijakan Pemasangan Pipa Gas Kodeco Energy Co. Ltd. di Alur Pelayaran Barat Surabaya - Malik, Djamaludin (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2019)
The installation of an underwater natural gas pipeline policy through the Strait of Madura conducted by Kodeco Energy Co. Ltd is to deliver gas from Poleng Processing Platform (PPP) oil and gas field on the offshore island of Madura to the Onshore Receiving Facility (ORF) in Gresik which will in use by five companies namely Perusahaan Listrik Tenaga Gas Gresik, Perusahaan Gas Negara, Petro Kimia, Media Karya Sentosa, and Gresik Migas. This study aims to evaluate the implementation of a license the Director General of Sea Transportation Agreement No: 771/9/5/DN-07 about Natural Gas Pipeline Underwater Installation Approval Kodeco Energy Co. Ltd. property, in particular relating to the position and placement of the gas pipeline through the Lanes of West Surabaya. The method used in this research is a method of qualitative analysis. The results of this study indicate that there is a difference between the position and placement of gas pipeline are permitted by the implementation of field installation, and can endanger the safety of ships through the shipping lanes of West Surabaya. From this research there are three alternative solutions proposed. The first alternative is to move all the pipelines to the west shipping lanes closer to the mainland coast in Gresik, while the second alternative is to move some pipelines that position in the shipping lanes across to the east of the mainland near the island of Madura and give pipelines concrete safety of ships fallout anchor hazard in most of the gas pipelines.